SEVERAL ISSUES ABOUT THE POETICS OF GORAN STEFANOVSKI’S ESSAYS (Journal of Contemporary Philology, 2021)
This research paper is dedicated to the essayistic work of Goran Stefanovski, which, so far, has not been studied and commented on by Macedonian literary scholars. Considering the essay as a specific genre, in the analysis of the poetics of Stefanovski’s essays, it is concluded that his essay text with its peculiarities,outperforms the previous theoretical features of the essay. Being a text that belongs to a meta-genre/supra-genre, Stefanovski’s essay cannot be strictly categorized only through the existing typologies, where it is, inter alia, recognized as a specific type of an essay – renaissance-postmodernist essay. Analyzing hispoetics, one could conclude that Stefanovski’s essayistic work advances from a mini or draft essay to a hyper essay, where like mise en abyme, several types of essays as structural parts of the essay are included, according to the existing typologies. The paper also points to the need for further readings and analyses in which other aesthetic and poetic dimensions of Stefanoski’s essay will be presented and evaluated, signaled by this dominant theoretical analysis.
Keywords: poetics; renaissance-postmodernist essay; Goran Stefanovski; categorization; meta-genre